Nutrition and Eye Health - Downie, Laura (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Blindness and visual impairment impact significantly on an individual's physical and mental well-being. Loss of vision is a global health problem, with approximately 250 million of the world's population currently living with vision loss, of which 36 million are classified as blind. Visual impairment is more frequent in the elderly, with cataract and age-related macular degeneration (AMD) accounting for over 50% of cases globally. Oxidative stress has been strongly implicated in the pathogenesis of both conditions, and consequently the role of nutritional factors, in particular carotenoids and micronutrient antioxidants, have been investigated as possible preventative or therapeutic strategies. Dry eye syndrome (DES) is one of the most common ophthalmic conditions in the world. DES occurs where the eye does not produce enough tears and/or the tears evaporate too quicklyleading to discomfort and varying degrees of visual disturbance. There has recently been a great deal of interest in the potential for oral or topical supplementation with essential fatty acids (EFAs), specifically omega-3 and omega-6 fatty acids, as an adjunct to conventional treatments for DES. The objective of this Special Issue on 'Nutrition and Eye Health' is to publish papers describing the role of nutrition in maintaining eye health and the use of nutritional interventions to prevent or treat ocular disease. A particular (but not exclusive) emphasis will be on papers (reviews and/or clinical or experimental studies) relating to cataract, AMD and DES.